2001
DOI: 10.1210/en.142.11.4956
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Pancreatic   Cells from Intra-Islet Precursor Cells in an Experimental Model of Diabetes

Abstract: We previously reported that new beta cells differentiated in pancreatic islets of mice in which diabetes was produced by injection of a high dose of the beta cell toxin streptozotocin (SZ), which produces hyperglycemia due to rapid and massive beta cell death. After SZ-mediated elimination of existing beta cells, a population of insulin containing cells reappeared in islets. However, the number of new beta cells was small, and the animals remained severely hyperglycemic. In the present study, we tested whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
160
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(176 citation statements)
references
References 0 publications
10
160
0
6
Order By: Relevance
“…It has been reported that amelioration of hyperglycemia such as insulin supplementation after STZ injection could accelerate the regeneration of b-cells. 9,22 In DDC-STZ-treated mice, we observed 10-fold increase of the hepatic insulin content per gram tissue, which is 43% of total pancreatic insulin at 14 days after STZ treatment ( Table 1). Considering that the blood glucose level was highest and the pancreata damaged by STZ had the lowest insulin contents at that time, the hepatic cells are thought to prevent excessive hyperglycemia, which would irreversibly damage the islet b-cells.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been reported that amelioration of hyperglycemia such as insulin supplementation after STZ injection could accelerate the regeneration of b-cells. 9,22 In DDC-STZ-treated mice, we observed 10-fold increase of the hepatic insulin content per gram tissue, which is 43% of total pancreatic insulin at 14 days after STZ treatment ( Table 1). Considering that the blood glucose level was highest and the pancreata damaged by STZ had the lowest insulin contents at that time, the hepatic cells are thought to prevent excessive hyperglycemia, which would irreversibly damage the islet b-cells.…”
Section: Discussionmentioning
confidence: 87%
“…8 However, the newly emerged insulin-producing cells in the pancreas and other organs are not sufficient in number as well as in insulin production ability to reverse the diabetic condition. 9 Although hyperglycemia is detrimental to islet bcells, high glucose is a very efficient signal in vitro for differentiation of stem cells into insulin-producing cells. 10,11 We hypothesized that if enough stem cells were activated before the diabetic induction, hyperglycemia could be ameliorated by these transdifferentiating stem cells.…”
mentioning
confidence: 99%
“…The origin of b-cell mass expansion, which is known to occur after partial pancreatectomy, 9 STZ, 10 or interferong, 11 has been a subject of recent controversy. Dor et al 12 concluded that new islets could only be formed by replication of existing b-cells after birth or partial pancreatectomy in adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that these adult pancreatic stem or progenitor cells reside in the epithelium of pancreatic ducts 5,6 , inside islets 7 or in the bone marrow 8 . Others have suggested that b-cells form in the adult by transdifferentiation of pancreatic acinar cells 9 , islet cells that express hormones other than insulin 10 , or splenocytes 11 . In addition to explaining the formation of new b-cells within existing islets, it has also been suggested that whole new islets form (islet neogenesis) by clustering of new b-cells that are derived from stem cells 5,12,13 .…”
mentioning
confidence: 99%